Pengaruh Perbandingan Tepung Talas Beneng (Xanthosoma Undipes K.Koch) dan Tepung Kedelai (Glicine Max L.Merrill) terhadap Karakteristik Kukis - Radityani, Ayu Cynthia Dewi; Putra, I Nengah Kencana; Permana, I Dewa Gde Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i03.p02, 2024)
Cookies are an alternative snack that is easy to find which has a small shape, crunchy texture with a sweet, savory and long-lasting taste. Generally, pastries are made from imported wheat. Reducing wheat consumption can be done by using local food ingredients such as beneng taro which is rich in nutritional content but low in protein. An effort to complement the nutritional content of cookies made from beneng taro flour is by adding soy flour. This research aims to determine the correct ratio of taro beneng flour and soybean flour so as to produce cookies with the best characteristics. The research design used was a Completely Randomized Design (CRD) with a treatment comparison of beneng taro flour and soybean flour consisting of 6 levels: 100%:0%, 95%:5%, 90%:10%, 85%:15%, 80%:10%, 75%:25%. There were 18 experimental units where each treatment was repeated 3 times. Next, the data was analyzed using variance and if the treatment had a real effect, Duncan's multiple range test was continued. The results of the study showed that the comparison of beneng taro flour and soybean flour had a significant effect (P<0.05) on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, texture hardness test, and hedonic test on color, aroma, taste, texture, and overall acceptability. A comparison of 85% beneng taro flour and 15% soybean flour has the best cookie characteristics with a water content of 2.53%, ash content of 2.59%, protein content of 7.35%, fat content of 33.38%, carbohydrate content of 54.14% , crude fiber content 5.46%, texture hardness test 76.25 N, sensory color, aroma, taste, texture and overall acceptance with the criteria of somewhat liking. Keywords: cookies, characteristics, beneng taro flour, soybean flour